Getting tired of work, or re-tiring in absence of decent job opportunities? Some insights from an estimated random utility/random opportunity model on Belgian data - Bart Capéau; André Decoster (University of Essex, Institute for Social and Economic Research (ISER), 2016)
This paper exploits the distinction between preference and opportunity factors in a Random Utility and Random Opportunity (RURO) model of job choice (Aaberge, Dagsvik and Strøm, 1995, and Aaberge, Colombino and Strøm, 1999). We estimate the model on Belgian data (SILC 2007). To investigate to what extent lower labour market participation of elderly is due to changing preferences (executing a job might become less enjoyable with age) or to differences in opportunities (elderly getting less, or less attractive job offers), we use the estimated model to simulate two counterfactuals. In the first, we remove partly the age heterogeneity in opportunities, in the second we remove age heterogeneity in preferences. A comparison of labour market behaviour in these two counterfactuals with the baseline shows that opportunities which decline with age are at least as an important factor in explaining low participation rates for the elderly, as is increasing preference for leisure. The effect of opportunities seems to work primarily through the extensive margin, whereas the effect of preferences is more outspoken in the intensive than in the extensive margin.
Keywords: J22; C25; H31; 330; discrete choice; labour supply; random utility model; opportunities